Stabilization of PET plastic-demolition waste blends using fly ash and slag-based geopolymers in light traffic road bases/subbases. (17th May 2021) - Arulrajah, Arul; Perera, Sahan; Wong, Yat Choy; Maghool, Farshid; Horpibulsuk, Suksun
Graphical abstract: Highlights: Fly ash (FA) and slag (S) based geopolymer stabilization of PET/C&D blends. Evaluation of geotechnical parameters of 5%PET blends with RCA and CB. Strength, stiffness and resilient properties of stabilized 5%PET blends with C&D. Bulk stress and three-parameter models of geopolymer stabilized PET/C&D blends. 10%S, 5%FA + 5%S blends satisfied UCS requirement for pavement base/subbase materials. Abstract: Polyethylene terephthalate (PET) plastic and construction and demolition (C&D) wastes contribute to a substantial fraction of the annual landfilling waste composition of the world. Substituting traditional road construction materials with PET/C&D blends is a sustainable solution for the increasing landfilling requirement and increasing demand for the natural quarry aggregates. This study evaluates the main geotechnical parameters of the geopolymer-stabilized blends comprising of two main C&D types, namely recycled concrete aggregate (RCA) and crushed brick (CB), in blends with 5% PET fragments (% by mass). 10%Fly ash (FA), 10%Slag (S) and 5%FA + 5%S were used as the precursors at a fixed liquid activator to precursor ratio of 0.4, and the alkaline activator for the geopolymer solution was comprised of 30:70 ratio of liquid NaOH:Na2 SiO3 solution. Strength and stiffness characteristics of the stabilized blends were evaluated by unconfined compressive strength (UCS) tests. The resilient modulus (MR ) values of the geopolymer-stabilized blends under different cyclic axial stresses and confining stresses were assessed by repeated load triaxial (RLT) tests. Bulk stress and three-parameter model parameters were determined from the RLT test data to predict the variation of MR of the geopolymer-stabilized PET/C&D blends. All the geopolymer-stabilized blends using 5%FA + 5%S and 10%S as precursors satisfied the minimum UCS limit of the granular materials for light traffic road bases/subbases. Geopolymer-stabilized PET/C&D was identified as a potential, sustainable option for the stabilization of upcoming road bases/subbases.